2013
DOI: 10.1158/1538-7445.am2013-lb-214
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-214: Common genomic alterations in malignant peripheral nerve sheath tumors augment Aurora A activity and sensitize tumors to aurora kinase inhibitors.

Abstract: Malignant peripheral nerve sheath tumours (MPNST) are rare, hereditary, cancers associated with mutations in the neurofibromin 1 gene 1. MPNSTs are often resistant to chemotherapies and have high rates of disease recurrence, highlighting the lack of effective treatment options for this cancer. Aurora kinase A inhibitors (AKIs) have shown promise against MPNST cell lines 2. We expanded this study by testing AKI in human MPNST xenotransplant mice models. Treatment resulted in stabilized disease with tumor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Assuming that these relative expression levels are reflected at the protein level, and considering that TPX2 and AURKA may act as a functional unit, this result implies that AURKA activation by TPX2 in PDAC is probably maximal due to the excess of TPX2. In fact, a higher TPX2 expression relative to AURKA has also been found in non-small cell lung cancer [42] and the level of TPX2 expression in malignant peripheral nerve sheath tumor cell lines has been found to positively correlate with AURKA activity [43]. In line with these observations, it has been found that the TPX2 expression level in non-hodgkin lymphoma cells may serve as a predictor of response to AURKA inhibition [44].…”
Section: Discussionmentioning
confidence: 71%
“…Assuming that these relative expression levels are reflected at the protein level, and considering that TPX2 and AURKA may act as a functional unit, this result implies that AURKA activation by TPX2 in PDAC is probably maximal due to the excess of TPX2. In fact, a higher TPX2 expression relative to AURKA has also been found in non-small cell lung cancer [42] and the level of TPX2 expression in malignant peripheral nerve sheath tumor cell lines has been found to positively correlate with AURKA activity [43]. In line with these observations, it has been found that the TPX2 expression level in non-hodgkin lymphoma cells may serve as a predictor of response to AURKA inhibition [44].…”
Section: Discussionmentioning
confidence: 71%